The symbolism of the student and the woman in the Arabic poem before Islam (Journal of the College of Basic Education, 2022)
Neither the ancient nor the modern critics agreed on an issue as they agreed on the quality of pre-Islamic poetry and the goodIts composition, the strength of its casting, the beauty of its images, the gentleness and sincerity of its meanings, the strength of its structure, and the depth of its connotations.Alone, the shadow of the kiss of Arab poets in their early and late ages, with which they take, and with which they become.And their example, which they are guided by, and their model is the best by which they follow and from which they draw. that the transferContemporaries differed in looking at the structure of the poem, as they differed about its performative formulation and its implications.artistic and objective, and they are of three types: a class he said: the realism of poetry